COMPUTER AIDED INSTRUCTIONAL MATERIALS IN TEACHING COOKERY IN GRADE 10: IT’S EFFECTIVENESS - nicolas, sharon (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2019)
Today’s world is known as the globalization era and is marked by rapid and complex changes both in social and values and learning structures. As such, it is natural for the education sector to review, update and orient their programs to the paradigm of these developments because education is crucial to global competitiveness and total human development. The main purpose/aim of this research is to determine the effectiveness of computer aided instructional materials in teaching cookery to grade 10 students. In this study, experimental method of research was used, the pretest and posttest design. The control group and the experimental group were both given a pretest, then exposed to different teaching methods. The experimental group was exposed to computer aided instructional materials while the control group was taught using the traditional approach. Both groups were given a posttest. The researcher used Mean, Percentage and T-test for the statistical treatment. Comparing the results of the pretest and posttest in the control and experimental group, it shows that students who used computer aided instructional materials performed well in class. The result of the experimental group increases in the post test. Therefore, computer aided instruction enhances the learning abilities of the students.